Kanstantsin Dzehtsiarou, Reforming the Election Process of Judges of the European Court of Human Rights (Reforma procesu wyboru sędziów Europejskiego Trybunału Praw Człowieka), „European Convention on Human Rights Law Review” 2023, no. 4(3), s. 231–239 - Dąbrowska, Anna (Studia Prawa Publicznego, 2024)
Przegląd wybranych czasopism zagranicznych: Kanstantsin Dzehtsiarou, Reforming the Election Process of Judges of the European Court of Human Rights (Reforma procesu wyboru sędziów Europejskiego Trybunału Praw Człowieka), „European Convention on Human Rights Law Review” 2023, no. 4(3), s. 231–239, https://doi.org/10.1163/26663236-bja10069 (opr. Anna Dąbrowska)